The interaction of tropomodulin with tropomyosin stabilizes thin filaments in cardiac myocytes - Mudry, Ryan E. (The Rockefeller University Press, 2003)
Actin (thin) filament length regulation and stability are essential for striated muscle function. To determine the role of the actin filament pointed end capping protein, tropomodulin1 (Tmod1), with tropomyosin, we generated monoclonal antibodies (mAb17 and mAb8) against Tmod1 that specifically disrupted its interaction with tropomyosin in vitro. Microinjection of mAb17 or mAb8 into chick cardiac myocytes caused a dramatic loss of the thin filaments, as revealed by immunofluorescence deconvolution microscopy. Real-time imaging of live myocytes expressing green fluorescent protein–α-tropomyosin and microinjected with mAb17 revealed that the thin filaments depolymerized from their pointed ends. In a thin filament reconstitution assay, stabilization of the filaments before the addition of mAb17 prevented the loss of thin filaments. These studies indicate that the interaction of Tmod1 with tropomyosin is critical for thin filament stability. These data, together with previous studies, indicate that Tmod1 is a multifunctional protein: its actin filament capping activity prevents thin filament elongation, whereas its interaction with tropomyosin prevents thin filament depolymerization.